Evaluasi Media Ajar AR Halo Kids Pada Anak Dengan Teknologi Augmented Reality Berbasis Android - Fendi Aji Purnomo; Eko Harry Pratisto; Firma Sahrul Fahrukan; Muhammad ‘Adli Zul Hazmi (IJAI (Indonesian Journal of Applied Informatics), 2017)
This study aims as an easy and inexpensive learning media that can be used to increase education for early childhood such as knowledge about the introduction of various professions. Media learning in the form of physical at this time is considered quite expensive, in addition to learning media in the form of physical need more understanding to be able to understand something learned.This research was developed with SDLC (System Development Life Cycle) method. This research includes the kind of augmented reality technology development that contains insight into the various professions, plants, musical instruments, and my needs. Objects taken about the character of the profession, the form of musical instruments, the shape of the plant, and the form of home appliances. Data collection techniques were conducted by questionnaire. Questionnaire is used to assess the completeness and feasibility of the application. Software engine that we use is unity game engine.The results of the research has been successfully created HALO KIDS applications in the form of 3D visual images of several themes including professions, needs, instruments, and plants. The HALO KIDS app is a file with a .apk extension. The HALO KIDS app runs optimally with a minimal smartphone specifying a 2.3 GHz Quad-core device (2 GB of RAM). The use of applications by children is easy to do with Agree-Strongly Agree value of 59%, 3D objects of the profession can be recognized and remembered by children with the value of agree- strongly agree at 67%.